Meio ambiente e representações sociais de pescadores - Pereira, Maracy (2013)
The central object of the research are the social representations of coastal fishermen on the changes in the environment, accompanied during the life trajectory of each individual research participant. It is the identification of concepts, ideas and images shared by fishermen about the changes in the local environment, primarily the river São Francisco and the analysis of the presence and influence of the life histories of coastal fishermen in the construction of such concepts, ideas and images shared. Participated in this study twenty fishermen aged between twenty-five and sixty-five years. The research was based on qualitative ethnography. The main instruments of data collection were the oral stories of life, and semi-structured interviews or focus group par. The results of this research highlight the value of life histories and the set of experience knowledge as sources of seminal readings on broader social issues, in particular to the field of interdisciplinary studies on development and the environment. In this situation, one can say that social representations of fishermen about the environment are intertwined in the cultural practice that originate, own express dynamism and strength of belonging, as well as consolidate the expression of identities-their singularities, without it them identical to each other, but authors of their own life stories, shared by the notion of community to which they belong. Social representations made explicit during the research for the dominance of shared beliefs about the legendary universe, the 'stories of fisherman' which effectively gave the characterization of the group understands the importance of them in their culture existential tensions experienced as denial-sharing , worldliness, sacredness, life-death, from-reach, change-reunion stay at São Francisco River with the life stories of fisherman.